Reducing Natrium Chloride Concentration by Using the Alkali from Banana Stems in Bracket Water - Inayah; Wahyuni Sahani; Syamsuddin S; Agus Erwin Ashari (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective: This study aims to reduce the concentration of sodium chloride using banana stem media with a thickness of 10 cm, 15 cm, and 20 cm. Method: This type of research is quasi-experimental research by conducting trials of hard water management using banana stem media with variations in the thickness of the media, namely 10 cm, 15 cm, and 20 cm by replicating 3 times. Sampling was carried out in rivers containing chloride levels in Makassar. The sampling method is using Grab Sample which is taken directly from a river flow which is classified as brackish water. The data analysis technique was carried out by using the ANOVA test. Result: The results obtained are banana stem media with a thickness of 10 cm can reduce levels of chloride (Cl) 2377, 69 mg/l, a thickness of 15 cm can reduce levels of chloride (Cl) 1772.27 mg/l, and a thickness of 20 cm can reduce levels of chloride (Cl) 1166.18 mg/l. Conclusion: The decrease in chloride levels in water is due to the presence of 4.60 grams of charcoal hydrate content in banana stems which functions to bind chloride levels in the water, besides that there is also a membrane in the banana stem in the form of cellulose which plays a role in binding chloride levels in water and also as an osmosing. Banana stalks can bind chloride levels.